1972
DOI: 10.1021/i260044a018
|View full text |Cite
|
Sign up to set email alerts
|

Oil Slick Removal Using Matrices of Polypropylene Filaments

Abstract: Use of matrices of polypropylene filaments in the removal of oil from the surface of seawater was investigated. The data indicated that the distance between the filaments and the cross-sectional area of the filaments was an important factor in the observed removal capacity of the matrices. An increase in the turbulence level of the slick surface markedly decreased the oil retention capabilities of the matrices. At similar interfilament distances, changes in the filament geometry from circular to rectangular le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…The ESEM observation made during the given time interval and analysis of micrographs indicated that the oil on the left migrated to the oil drop on the right position. Considering the high degree of crystallinity of PP sheath fiber, absorption into the fiber is less likely as pointed out by previous studies (Zahid et al, 1972;Fig. 13.…”
Section: Man-made Sorbent Materialsmentioning
confidence: 86%
“…The ESEM observation made during the given time interval and analysis of micrographs indicated that the oil on the left migrated to the oil drop on the right position. Considering the high degree of crystallinity of PP sheath fiber, absorption into the fiber is less likely as pointed out by previous studies (Zahid et al, 1972;Fig. 13.…”
Section: Man-made Sorbent Materialsmentioning
confidence: 86%
“…The increased sorption happened due to the adherence of the oil to the fibre's surface whereas the decreased sorption occurred when oil is inhibited from penetrating the interior of the fibre (Ceylan et al, Choi and Moreau, 1993;Wei et al, 2003;Zhu et al, 2011). Here, it can be seen that macroporous materials play an important role to determine the sorption capacity for oil of different viscosity (Ceylan et al, 2009;Zahid et al, 1972;Zhu et al, 2011).…”
Section: Oil Viscositymentioning
confidence: 95%
“…Next, the Cholan pieces were lifted by a wire basket and allowed to drip freely for 1 min before being finally weighed. Previous researchers suggested this 1-min free dripping (Choi, 1996;Johnson et al, 1973;Radetić et al, 2003;Zahid et al, 1972). Cholan was centrifuged in order to separate the water and oil.…”
Section: Selectivity Testmentioning
confidence: 99%